The Influence of Sentiment on Social Media Mentions on National Board of Zakat (BAZNAS) Fundraising During the Palestine War - Arpenta, Shady (ITQAN: Journal of Islamic Economics, Management, and Finance, 2025)
This study aims to evaluate the effect of sentiment in social media mentions on the success of BAZNAS fundraising efforts related to the Palestinian issue. The sentiment analysis method was employed to measure the sentiments expressed in social media mentions related to the Palestinian issue and BAZNAS fundraising. All mentions made between October 7 and December 31, 2023, were collected to be classified based on positive and negative sentiments using the Astramaya platform. The results of this sentiment classification were then analyzed using the Pearson correlation test method. The results showed that positive sentiment on social media mentions had a significant positive influence on the success rate of BAZNAS fundraising. Conversely, negative sentiment hurts fundraising success. This review can serve as a strategic reference for non-profit organizations in managing their brand and image through social media during sensitive or controversial situations.